Malaysian students’ perceptions towards using peer feedback to cultivate evaluative judgement of argumentative writing - Xie, Xiao; Nimehchisalem, Vahid; Yong, Mei Fung; Yap, Ngee Thai (Arab World English Journal, 2024)
Although peer feedback is a prevailing practice to promote evaluative judgement, its influence on the development of this higher-order cognitive ability has not yet been adequately explored. Specifically, there is a dearth of research that examines the benefit of providing and receiving peer feedback in developing students’ understanding of assessment standards of writing. The purpose of this study is to explore students’ perceptions of how different feedback roles influenced their three types of evaluative judgement of ESL argumentative writing, namely hard, soft and dynamic evaluative judgement. During five weeks, 24 undergraduate students enrolled in an English argumentative writing course at a Malaysian public university were randomly assigned to three distinct peer feedback roles, namely feedback provider, feedback receiver, or feedback outsider, to participate in the peer feedback activities. Thematic analysis of pre- and post-intervention surveys indicated that different feedback roles varied in facilitating the development of evaluative judgement. Despite the limitation of domain-specific knowledge, strategically integrating peer feedback into writing course design afforded students opportunities to cultivate the three types of evaluative judgement. This study translates the theoretical framework of evaluative judgement into identifiable goals within the course of English argumentative writing and sheds light on the cognitive mechanisms inherent in different feedback roles, which enables educators and researchers to better dissect peer feedback curriculum design and student-centred assessment activity.